IMPLEMENTASI KURIKULUM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR - Agus Hermawan; Ifah Khadijah; Usep Suherman; Aceng Nurulhuda (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the implementation of the curriculum in higher education institutions based on the Independent Learning–Independent Campus (MBKM) policy, with a focus on the Elementary School Teacher Education (PGSD) Study Program at Mandiri University, Bandung. The MBKM policy, launched by the Ministry of Education, Culture, Research, and Technology, aims to provide flexibility and freedom for students to develop their potential, competencies, and skills across disciplines through learning outside of their study program. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The results show that the implementation of MBKM has had a positive impact on student competency development, particularly in terms of improving soft skills, contextual experiences, and readiness for the world of work. Overall, the MBKM curriculum encourages a more adaptive, collaborative, and relevant learning transformation to meet current needs. Therefore, strengthening academic governance, synergizing with stakeholders, and updating the curriculum are crucial to supporting the sustainability of the MBKM program in higher education institutions.